Smart Linen Hamper and Laundry Monitoring for Hospital Industry - Mohd Zainordi, Muhamad Syahmi; Ubin, Aizan (Evolution in Electrical and Electronic Engineering, 2024)
This project creates an efficient and reliable smart linen hamper and laundry monitoring system using IoT. One output from four scale load cells and a HX711 module allows a Smart Linen Hamper system to accurately assess linen load. The mux and HX711module select a combination output channel. This system will monitor linen capacity and alert users via Blynk to avoid overloading. Overloading can degrade washing, resulting in unclean clothes and stressed machine parts, increasing maintenance costs and equipment lifespan. Blynk’s real-time tracking improves laundry monitoring. Without it, hospitals waste resources and operate inefficiently. A smart linen hamper and laundry monitoring system with IoT notifications improves hospital laundry management by being efficient, accurate, and proactive. Patients receive better care, hospitals run more efficiently, and physical work diminishes. Administration of laundry by this technology decreases human errors and enhances hospital linen management.